PROFIL BALITA STUNTING DI WILAYAH KERJA PUSKESMAS KENJERAN KOTA SURABAYA - Dwi Ernawati; Diyah Arini (Jurnal Kesehatan Mesencephalon, 2020)
Stunting is a chronic malnutrition with a short child's body to exceed the deficit of 2 elementary school under the median length or height of the population which is an international reference due to lack of nutrient intake for a long time. Stunting in toddlers is usually not realized by parents, because differences in height with normal-age children are less visible. The purpose of this study is to provide an overview of the incidence of stunting toddlers in the working area of the Kenjeran Public Health Center in Surabaya.The research design used descriptive method with a sample of 145 respondents mothers and children under five 2-5 years in the working area of the Kenjeran Health Center in Surabaya, namely in 4 Kelurahan namely Kenjeran Kelurahan, Sukolilo Kelurahan, Bulak Kelurahan, and Kedung Cowek Kelurahan. The research variable is the incidence of stunting toddlers with height measurements using microtoise sampling technique using stratified random sampling with tabulation of frequency distribution.The results showed that stunted children under five were 95 children (64.5%), and stunted children were very short (severe stunted) as many as 50 children (34.5%).This study is useful as a motivation for parents with minimal family income but does not reduce the supply of balanced nutrition in children. Nutritious food that is cheap and a good way of processing food. Parents understand the stunting experienced by toddlers and are able to apply good nutrition in an effort to minimize the number of stunting events. Keywords:  Under five year old,  StuntingAbstrak : Stunting adalah kondisi tubuh yang pendek  yang ditandai dengan panjang atau tinggi badan menurut usia dibawah standar (< -2 SD) di bawah median yang mengakibatkan gangguan pencapaian tinggi badan normal sesuai usianya. Kejadian Stunting sering tidak menjadi perhatian orang tua, karena tidak terlihat perbedaan pada  tinggi badan balita stunting dibandingkan anak  sehat. Tujuan penelitian ini adalah memberikan gambaran kejadian balita stunting di wilayah kerja puskesmas Kenjeran Kota Surabaya.Disain penelitian menggunakan metode eksploratifdengan jumlah sampel 145 responden  ibu dan anak balita 2-5 tahun di wilayah kerja puskesmas Kenjeran Kota Surabaya. Variabel penelitian adalah kejadian balita stunting  dengan pengukuran tinggi badan menggunakan microtois. Tekhnik sampling menggunakan stratified random sampling dengan tabulasi distribusi frekuensi. Hasil penelitian menunjukkan bahwa balita stunting kategori pendek (stunted) yaitu sebanyak 95 balita (64,5%), dan balita stunting kategori sangat pendek (severe  stunted) sebanyak 50 balita (34,5%).Tenaga kesehatan dapat memberikan edukasi melalui posyandu agar orang tua paham tentang stunting dan dapat menyediakan nutrisi seimbang pada anak meskipun pendapatan minimal. Makanan bergizi yang harganya murah dengan cara pengolahan makanan yang baik dapat  meminimalisir angka kejadian stunting. Kata kunci : Balita, Stunting